Fraud Prevention Village Fund Management: Village Apparatus Competence, Integrity, and Individual Morality - Khairun Nisa; Ansar, Muhammad; Abdullah, Muhammad Ikbal; Tanra, Andi Ainil Mufidah (Lembaga Riset Ilmiah, 2025)
This study aims to examine the effect of village apparatus competence, integrity, and individual morality on preventing fraud in village fund management in the Village Government in Marawola Sub-district. This research uses quantitative methods. The population of this study were 11 villages in Marawola District, Sigi Regency and the sample used in this study were 88 people selected using saturated sampling technique consisting of village heads, secretaries, and heads of affairs and section heads. The data used in this study are primary data collected using questionnaires. This analysis uses multiple regression analysis techniques using the SmartPLS 4 application. The results showed that the competence of village officials and integrity had no significant effect on preventing fraud in village fund management, while individual morality had a significant effect on preventing fraud in village fund management. This research shows that individual morality internalized in the village apparatus is a key factor in suppressing the potential for fraud, while village apparatus competence and integrity are not strong enough if not accompanied by high moral values.